Pulsed‐CO2 Laser Beam Photothermal Technology Combined with Conjugated Gold Nanoparticles for the Selective Elimination of Surface Escherichia Coli K12 from Fresh Fruits. Issue 5 (29th December 2014) - Chee, Grace; Shafel, Timothy; Park, Sung Hee; Jun, Soojin
Abstracts Postharvest methods for microbial decontamination of fresh produce are limited, and chemical treatment is less popular with growing concerns over toxic residues. A photothermal guiding system was developed with a pulsed‐CO2 laser and adjustable two‐ZnSe lens beam expander. The system was optimized to ensure uniform radiation of the sample with respect to pulse width (PW) and repetition time (RT) without damaging the food samples. Conjugated gold nanoparticles (GNPs) added to fruit surfaces tested the selective photothermal nanotherapy under laser radiation for enhancing treatment. Apple peel samples (1 cm2) contaminated with Escherichia coli K12 were treated at varying PW and RT for 60, 120 and 180 s. Inactivation of E. coli K12 significantly (P < 0.05) increased as the PW increased at constant RT. Also, the inactivation increased as both RT decreased and PW increased, and with the addition of the GNP. Scanning electron microscopy analysis showed structural damage of E. coli and GNP with minimal damage to fruit surfaces. Practical Applications This unique laser system could provide rapid, energy‐efficient and selective inactivation of food surface contaminants through the use of conjugated gold nanoparticles. The system's likely application is to ensure food safety in numerous segments of the U.S. food industry; it would be especially useful for producers of fresh food products. Photothermal nanotherapy provides selective heating to a localized area around the targeted bacteria without damaging the food, which makes it particularly applicable for heat‐sensitive foods, such as fruits and leafy green vegetables, and could be a desirable alternative to chemical treatments. It also has the potential to be successfully applied to liquid food samples such as water, fruit juices and other transparent liquids.